The Efficacy and Safety of Lenalidomide plus Rituximab in an Orbital Relapse of Diffuse Large B-Cell Lymphoma - R. Palmieri; F. Esposito; F. Meconi; V. M. Rapisarda; L. Anemona; G. Paterno; S. Vaccarini; D. Nasso; L. Pupo; M. Cantonetti (Case Reports in Hematology)
A 74-year-old male with diffuse large B-cell lymphoma, with an Ann Arbor stage IV-A, was submitted to immune-chemotherapy in 2014, with complete remission of the disease. Two years later, he presented with a left eye swelling leading to exophthalmos and blurred vision. A core biopsy was performed and revealed a local relapse of the disease. He was considered unfit for intensive salvage chemotherapy and was treated with a combination of rituximab and lenalidomide. After six courses of rituximab plus lenalidomide, the patient showed complete remission and was submitted to maintenance therapy with lenalidomide. After 24 months since the start of lenalidomide monotherapy, we did not observe any progression. In this experience, rituximab plus lenalidomide, without radiotherapy, was a safe and effective therapeutic combination in an elderly patient with a localized relapse of DLBCL who was unfit to receive more aggressive therapies.